2007
DOI: 10.1155/2007/15925
|View full text |Cite
|
Sign up to set email alerts
|

New Samarium(III), Gadolinium(III), and Dysprosium(III) Complexes of Coumarin‐3‐Carboxylic Acid as Antiproliferative Agents

Abstract: New complexes of samarium(III), gadolinium(III), and dysprosium(III) with coumarin-3-carboxylic acid (HCCA) were prepared by the reaction of the ligand with respective metal nitrates in ethanol. The structures of the final complexes were determined by means of physicochemical data, elemental analysis, IR and Raman spectra. The metal-ligand binding mode in the new Ln(III) complexes of coumarin-3-carboxylic acid was elucidated. The vibrational study gave evidence for bidentate coordination of CCA− to Ln(III) io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 27 publications
(33 reference statements)
1
41
0
Order By: Relevance
“…Interestingly, the m C@O (lactone) stretching vibration was shifted in all of the complexes by 11-56 cm À1 relative to the free ligand, upon formation of the Ag(I) complexes as was observed in the coumarin-3-carboxylates. Several reports have attributed such a shift to the participation of the coumarin lactone carbonyl in complexation to the metal ion [37][38][39] but it has also been reported for other coumarin derivatives where the lactone was not involved in complexation [40,41]. In the latter instance the shift may be attributed to an increase in polarity of the lactone ring which can occur upon metal complexation.…”
Section: Ir Spectramentioning
confidence: 88%
“…Interestingly, the m C@O (lactone) stretching vibration was shifted in all of the complexes by 11-56 cm À1 relative to the free ligand, upon formation of the Ag(I) complexes as was observed in the coumarin-3-carboxylates. Several reports have attributed such a shift to the participation of the coumarin lactone carbonyl in complexation to the metal ion [37][38][39] but it has also been reported for other coumarin derivatives where the lactone was not involved in complexation [40,41]. In the latter instance the shift may be attributed to an increase in polarity of the lactone ring which can occur upon metal complexation.…”
Section: Ir Spectramentioning
confidence: 88%
“…Additionally, evidence is rising that many REE exhibit anti-cancerogenic properties [24][25][26][27] . Therefore, magnesium alloys containing REE could be of particular interest for bone cancer treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In biomedical application, use of RE compounds should also be considered from the perspective of their potential cytotoxicity. Anti-carcinogenic properties of REs has been shown in number of studies [18][19][20][21], however some studies have also reported cytotoxic and hepatotoxic effects at high dose [22][23][24][25]. It has been shown that rare-earth alloying elements including Ce, Nd, Y, and Yb have no adverse effect on growth of living cells but they can induce inflammatory effects at high concentration [26].…”
Section: Introductionmentioning
confidence: 99%